Enhancing Branding Strategies of Culinary Micro and Small Enterprises through Online Media: A Community Service Approach: Meningkatkan Strategi Branding Usaha Mikro dan Kecil Kuliner Melalui Media Online: Sebuah Pendekatan Pengabdian Kepada Masyarakat - Maulana, Mahesa; Megantoro, Adrian Yohana; Setiawan, Azizah Nafabilla (Universitas Muhammadiyah Sidoarjo, 2023)
The marketing and product development of Micro and Small Enterprises (UMK) greatly rely on effective branding strategies. However, the utilization of online media for branding purposes is often lacking among MSE entrepreneurs. This community service initiative aimed to enhance the understanding and proficiency of UMK culinary product branding implementation in Karanganyar District, Karanganyar Regency, Central Java. The methodology involved short training and mentoring sessions for MSEs, focusing on three culinary business units, to design and develop marketing platforms through online media. The outcome of this activity demonstrated a significant improvement in MSEs' ability to leverage online media for branding their business products, as evidenced by the creation of various platforms such as e-commerce, Instagram, and TikTok. Implementing effective branding strategies through online media platforms has empowered MSEs to achieve optimal competitiveness in their respective culinary businesses. This study offers valuable insights and implications for researchers and professionals worldwide, highlighting the potential of online media in enhancing branding efforts for Micro and Small Enterprises in the culinary industry. Highlight: Community service enhances UMK entrepreneurs' understanding and implementation of branding through online media. Increased proficiency in utilizing platforms like e-commerce, Instagram, and TikTok. Optimal competitiveness and business development in the culinary industry. Keyword: Branding, Micro and Small Enterprises (UMK), Online Media, Culinary Products, Community Service